PENGEMBANGAN BUKU CERITA BERGAMBAR BERBASIS KEARIFAN LOKAL UNTUK MENINGKATKAN KEMAMPUAN LITERASI DASAR ANAK - Krismayanti, Yunita Riza Kurnia; Laila, Alfi; Kurnia, Ita (STKIP Pesisir Selatan, 2022)
This study aims to determine the validity, effectiveness and practicality of the product development of picture book media based on local wisdom. The type of research is development research (R&D) with the type of ADDIE research model. Product trials were conducted using limited and extended trials. The research subjects were on a small scale in the fourth grade of SDN Mrican 1, which amounted to 10 students, while the subjects of the large-scale trial were conducted on the fourth grade students of SDN Mrican 2, which amounted to 43 students. The feasibility analysis test of the product developed was determined through the results of material validation, media validation, and the practice of trial use by students and teachers using descriptive analysis. Test the effectiveness and practicality using a t-test using a questionnaire. The results of the study show (1) product validity scores 92 very valid categories, while material validation scores 89 very valid categories. (2) Product effectiveness gets an average score of 88 in the effective category. (3) The practicality of the product received a score of 92 very practical categories. It can be concluded that the development of picture book media based on local wisdom is very feasible to use in the learning process and can improve learning outcomes for students in learning material